(untitled) (Journal of the College of Education for Women, 2019)
The purpose of this research its study of Natural Consideration that contributed in turning of Dairy products in Baghdad Governorate , this subject deal with centered geographical location in the midlle of Iraq ,it’s also main market in discharge and marketing to rest of Iraqi’s governorate pointed to it’s an active role in localized of it’s factory(milk ,cheese,cream ,butter, yoghurte)and it’s constant ,thus distributedin all district of Baghdad ,flat governorate surface encourage this industry ,also climate (temperature, wind, (it’s speed and it’s direction) ,rainfull and relative wet) also water resources and it’s influenced that nessacity of production process with important inculclusion that researcher came out through the details of those consideration.